Stalingrad to Berlin : the German defeat in the east - Ziemke, Earl F., 1922-2007. (Washington, D.C. : Office of the Chief of Military History, U.S. Army : For sale by the Supt. of Docs., U.S. Govt. Print. Off., 1968)
The Russo-German war from Stalingrad to Berlin. Topics include strategy and tactics, partisan and psychological warfare, coalition warfare, and manpower and production problems faced by both countries.
Invasion! -- Retreat -- Stalingrad: the encirclement -- Stalingrad: the turning point -- The countermarch -- The Center and the North -- Operation Zitadelle -- The first Soviet summer offensive -- The battle for the Dnepr Line -- The rising tide -- Offensives on both flanks: the South Flank -- Offensives on both flanks: the North Flank -- Paying the piper -- The collapse of the Center -- The South Flank -- Retreat and encirclement -- Defeat in the North --The January offensive -- The defense of the Reich -- Berlin -- Conclusion -- APPENDIX: A: Table of equivalent ranks -- Comparative sizes of major commands.
Large 8vo.
Document for sale by the Superintendent of Documents, cloth, $4.50.
Includes bibliographical references and index.
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- Eastern Front; Guerre mondiale, 1939-1945 -- Campagnes et batailles -- Front oriental; Military campaigns; World War, 1939-1945 -- Campaigns -- Eastern Front; Eastern Front (World War (1939-1945)); World War, 1939-1945 -- Campaigns -- Eastern Front